Dampak Kerjasama AFTA dan Indonesia Terhadap Pemulihan Perekonomian Pasca Covid-19 - Nugraha, Mauludy Nugraha (Politeia: Jurnal Ilmu Politik, 2023)
The ASEAN Free Trade Area (AFTA) is an economic and trade cooperation agreement consisting of ASEAN countries. AFTA aims to realize increased trade cooperation by establishing a free trade area in an effort to increase the regional economic competitiveness by making ASEAN a global production center. This cooperation, which was formed to mutually encourage the country's economic growth, will be very useful, especially when the Covid-19 pandemic hit the world. Declining economic conditions due to Covid-19 have forced all countries to carry out economic recovery in order to create post-Covid-19 economic growth. So with that, the authors conducted a study entitled "The Impact of AFTA and Indonesia Collaboration on Post-Covid-19 Economic Recovery". The purpose of this research is to find out the impact resulting from the AFTA cooperation on post-Covid-19 economic recovery. The research method used by researchers is a qualitative method, namely by collecting data through analysis and literature study. From the results of research based on literature, it can be interpreted that the existence of this AFTA cooperation is sufficient to help the economy in Indonesia.